2009
DOI: 10.1161/circresaha.109.199471
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the CXC Chemokine Interferon-γ-Inducible Protein 10 Regulates the Reparative Response Following Myocardial Infarction

Abstract: Key Words: infarction Ⅲ remodeling Ⅲ chemokines Ⅲ fibrosis Ⅲ wound healing M yocardial infarct healing is dependent on activation of an inflammatory cascade, followed by granulation tissue formation and deposition of collagen-based matrix. 1,2 Rapid induction of inflammatory chemokines, cytokines and adhesion molecules in the infarcted myocardium results in chemotactic recruitment of leukocytes. Neutrophils and activated macrophages clear the wound from dead cells and debris while secreting mediators that prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 28 publications
1
105
1
1
Order By: Relevance
“…Interestingly, several studies have demonstrated an important role for IFN signaling in the activation and recruitment of Tregs to injured tissue (45,46,59,60). IFN-γ has been shown in prior studies to affect multiple pathways, including suppression of fibrosis in chronic myocarditis by reducing profibrotic cytokine secretion (61), as well as mediation of basic FGF-induced (bFGF-induced) fibroblast migration via CXCL10 (62). Recently, however, Tregs have been shown to express the IFN-γ-specific receptors IFN-γR1 and IFN-γR2, thereby allowing a subset of these cells to be mediated directly by the chemokine IFN-γ (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated an important role for IFN signaling in the activation and recruitment of Tregs to injured tissue (45,46,59,60). IFN-γ has been shown in prior studies to affect multiple pathways, including suppression of fibrosis in chronic myocarditis by reducing profibrotic cytokine secretion (61), as well as mediation of basic FGF-induced (bFGF-induced) fibroblast migration via CXCL10 (62). Recently, however, Tregs have been shown to express the IFN-γ-specific receptors IFN-γR1 and IFN-γR2, thereby allowing a subset of these cells to be mediated directly by the chemokine IFN-γ (45).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 has been described previously as a potent chemokine for attracting inflammatory cells, especially monocytes and T lymphocytes 12,22 but has also been associated with angiogenesis in the ischemic myocardium after induction of MI in mice. 21 In this study, we investigated the causal role of CXCL10 for perfusion recovery in a mouse model for hindlimb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular (LV) dimensions were measured in parasternal long-axis view using 2D-directed M-mode echocardiography as previously described (Bujak et al 2009). The following parameters were measured as indicators of LV function and remodeling: LV end-diastolic diameter (LVEDD), LV end-systolic diameter (LVESD), and fractional shortening (FS = 100 × [LVEDD -LVESD]/ LVEDD).…”
Section: Echocardiographymentioning
confidence: 99%